Pembiasaan Positif Shalat Berjamaah terhadap Karakter Spiritualitas Anak Sekolah Dasar - Muhammad Aslam Muamar; Sierra An Nadia; Maulida Rahmalia Putri; Lutfiah Lutfiah; Dina Luthfiana (Journal Innovation In Education, 2025)
This study aims to analyze the effect of positive habituation of congregational Zuhur prayer on improving the spiritual character of elementary school children. The research was carried out with a qualitative method through participatory observation at SDN Tugu Rejo 02, where the researcher participated in religious activities with students. The results of the study showed that regular congregational prayer activities had a positive impact on the development of students' disciplined attitudes, spiritual awareness, and polite behavior. This habituation is an effective means of forming religious values from an early age and encouraging the deep internalization of spiritual character. It can be concluded that the habituation of congregational worship is a relevant and applicable character formation strategy in the elementary school environment.